Dimensi Spiritual-Intelektual Filsafat Mulla Sadra Dan Kontekstualisasinya Bagi Kehidupan Modern - M. Zainal Abidin (Millah: Journal of Religious Studies, 2004)
This paper tries to discuss the main Muslim philosopher thought after Averroes, that's Mulla Sadra. As for  commonly many researchers of  Muslim intellectualism tradition, Sadra was not a strange people. The interesting thought from the philosophy of  Sadra was his spirit to combine the strength both spirituality and intellectuality together in searching the knowledge: The peripatetic and illumination in Islamic philosophy were combined with the Syi’i theology and the unity of  being of  Ibn ‘Arabi. For Sadra, both spiritual and intellectual dimension were two important entities in reaching the highest wisdom. The research of  Sadra thought also describes how to actualize in praxis modern life, which in  fact  still actual and relevant to be developed.